1992
DOI: 10.3168/jds.s0022-0302(92)77745-5
|View full text |Cite
|
Sign up to set email alerts
|

Response of Dairy Cows to High Doses of a Sustained-Release Bovine Somatotropin Administered During Two Lactations. 2. Health and Reproduction

Abstract: Eighty-two lactating Holstein cows in their first, second, or third lactation received either one, three, or five concurrent i.m. injections of a unit dose (.6 g) of zinc methionyl bST (sometribove) or five doses of the vehicle. Injections were given at 14-d intervals from 60 +/- 3 d postpartum until the end of lactation or necropsy. Thirty-eight animals were continued on treatment for a 2nd yr. Sometribove did not affect the incidence of ketosis, milk fever, tetany, or pneumonia. Digestive disorders, primaril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(14 citation statements)
references
References 18 publications
1
12
0
1
Order By: Relevance
“…At the same time, Esteban et al (1994) reported that because rates of dystocia and retained fetal membranes increased in control and rbSTtreated cows, exposure to rbST was probably not directly related to those changes. The observation that rbST did not increase the risk for a cow developing cystic structures during the early postpartum period of the following lactation agreed with similar finding reported by Cole et al (1992). Also, Lucy et al (1991) noticed that rbST may have a direct effect on ovarian tissues.…”
Section: Effect Of Rbst On Reproductionsupporting
confidence: 88%
“…At the same time, Esteban et al (1994) reported that because rates of dystocia and retained fetal membranes increased in control and rbSTtreated cows, exposure to rbST was probably not directly related to those changes. The observation that rbST did not increase the risk for a cow developing cystic structures during the early postpartum period of the following lactation agreed with similar finding reported by Cole et al (1992). Also, Lucy et al (1991) noticed that rbST may have a direct effect on ovarian tissues.…”
Section: Effect Of Rbst On Reproductionsupporting
confidence: 88%
“…Previous studies showed that rbST treatment in postpartum dairy cows can negatively affects estrous expression and reproductive performance (Cole et al, 1992;Kirby et al, 1997a;Santos et al, 2004). Nevertheless, prepartum rbST treatment improved ovulation and steroidogenesis of the first postpartum dominant follicle in dairy cows (Schneider et al, 2012;Acosta et al, 2017).…”
Section: Discussionmentioning
confidence: 93%
“…Peripartum rbST treatment promotes an increase in serum IGF-I concentration (Carriquiry et al, 2009) and glucose, and a decreased serum non-esterified fatty acids and beta-hydroxybutyrate concentration (Putnam et al, 1999). Despite positive effects on lactation, some studies suggest that rbST negatively affects reproductive performance in dairy cows in the long term (Cole et al, 1992;Kirby et al, 1997b;Santos et al, 2004). Interestingly, the prepartum treatment with rbST was associated with a shorter interval between calving and first ovulation in dairy cows (Schneider et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Do ponto de vista reprodutivo, em revisão de literatura sobre a utilização de rBST em vacas lactantes, Mattos (1998) (EPPARD et al, 1987;COLE et al, 1992;BAUMAN, 1999), enfermidades podais (CHALUPA et al, 1988) ou enfermidades hepáticas , já Etherton e Bauman (1998) afirmam que a dependência do estágio de lactação, a dose de somatotropina utilizada e o balanço energético das vacas, poderiam ser relacionados a transtornos na saúde desses animais.…”
Section: Lista De Tabelasunclassified